Relationship Between Nutrion Intake, Family Income and Stress Levels With Obesity In Adolecents: Hubungan Asupan Gizi, Pendapatan Keluarga, dan Tingkat Stres Dengan Obesitas Pada Remaja - Firdausi Ramadhani; Herman Hatta; Nuryani; Nirmala Yusuf; Suwignyo (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2021)
Background: Obesity is defined as an increase in energy intake compared to energy expenditure resulting in body fat deposits and eventually weight gain. The prevalence of obesity has increased sharply in the Asia Pacific region. Many factors cause obesity. Based on data obtained from the Gorontalo District Health Office in 2018, it showed that the incidence of obesity was 8.795 cases (30.9%) consisting of 1,971 cases of men (6.9%) and 6,824 cases of women (24.0%). Purpose: The purpose of the study was to see the correlation of nutritional intake, family income, and stress levels with the incidence of obesity in adolescents. Research methods: This type of research uses observational analytic research with a cross sectional study design. With data analysis techniques using Chi Square test. The population in this study were all teenagers in Bunto Village, East Popayato District, Pohuwato Regency. By using exhaustive sampling sampling technique. Research result : Based on the research results of energy intake with obesity obtained p value ((0,320>α(0,05)). Protein intake with obesity obtained p value ((0,599>α(0,05)). Fat intake with obesity obtained p value ((( 0.108>α(0.05)).Carbohydrate intake with obesity, obtained p value ((0.353>α(0.05)). Income with obesity obtained p value ((0.160>α(0.05)). Stress level with the incidence of obesity obtained p value ((0.645>α(0.05)). Conclusion : It was concluded that nutrient intake, income and stress levels were not correlated with the incidence of obesity in adolescents. As a suggestion to continue to provide information about the importance of maintaining nutritional intake in every food consumed